Vericiguat and transcatheter edge-to-edge mitral valve repair for combined post- and pre-capillary pulmonary hypertension due to left ventricular low ejection fraction and functional mitral regurgitation - Murakami, Tsutomu; Ohno, Yohei; Horinouchi, Hitomi; Noda, Satoshi; Hashimoto, Kaho; Miyamoto, Junichi; Kamioka, Norihiko; Natsumeda, Makoto; Tanaka, Shigemitsu; Ikari, Yuji (Journal of cardiology cases, 2024)
A 66-year-old female was diagnosed with combined post- and pre-capillary pulmonary hypertension due to heart failure with reduced ejection fraction (47 %) and functional mitral regurgitation [mean pulmonary arterial wedge pressure: 27 mmHg; pulmonary arterial pressure: 91/30 (56) mmHg; pulmonary vascular resistance: 12.9 Wood units; and cardiac index: 1.77 L/min/m2]. Following treatment with vericiguat (a novel oral soluble guanylate cyclase stimulator), hemodynamics improved [mean pulmonary arterial wedge pressure: 27 mmHg; pulmonary arterial pressure: 54/26 (35) mmHg; pulmonary vascular resistance: 2.2 Wood units; and cardiac index: 2.80 L/min/m2]. Therefore, transcatheter edge-to-edge repair for functional mitral regurgitation was performed. One month later, further improvement in hemodynamics was confirmed. Vericiguat (a novel oral soluble guanylate cyclase stimulator) and transcatheter edge-to-edge mitral valve repair may improve combined post- and pre-capillary pulmonary hypertension due to low ejection fraction of the left ventricle and functional mitral regurgitation.